1996
DOI: 10.1080/00039896.1996.9934427
|View full text |Cite
|
Sign up to set email alerts
|

Is Placenta a Good Indicator of Cadmium and Lead Exposure?

Abstract: Distribution of lead and cadmium was studied in 25 placentas. Samples were taken from 6 different lobuli, and lead and cadmium concentrations were not determined by graphite furnace atomic absorption spectrometry. Lead and cadmium were not distributed uniformly, and the concentrations differed by a factor > or = 2 among different lobuli within the same placenta in 36% and 52% of the placentas, respectively. Placental lead and cadmium concentrations were also determined in homogenized samples from smelter (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
5
32
1
Order By: Relevance
“…No di erences existed for other analyzed trace elements in the placentas, iron and copper. The initial result was expected, as placenta has been considered as an indicator tissue for cadmium exposure (Baglan et al, 1974;Lagerkvist et al, 1996;Piasek et al, 2001Piasek et al, , 2002. Concentrations of placental metals in this study fall within the ranges of those reported for other urban areas (Reichrtová et al, 1998a, b;Osman et al, 2000;Zadorozhnaja et al, 2000;Falcon et al, 2002;Odland et al, 2003;Ronco et al, 2005;Sorkun et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…No di erences existed for other analyzed trace elements in the placentas, iron and copper. The initial result was expected, as placenta has been considered as an indicator tissue for cadmium exposure (Baglan et al, 1974;Lagerkvist et al, 1996;Piasek et al, 2001Piasek et al, , 2002. Concentrations of placental metals in this study fall within the ranges of those reported for other urban areas (Reichrtová et al, 1998a, b;Osman et al, 2000;Zadorozhnaja et al, 2000;Falcon et al, 2002;Odland et al, 2003;Ronco et al, 2005;Sorkun et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Of the two toxic metals that we assessed in placental tissue, it is well known that, as a consequence of exposure, increased concentrations of lead can be measured in umbilical cord blood and other fetal body compartments following its passage of the placental barrier. That is quite di erent than for cadmium, which accumulates in placental tissue as retained by the placental barrier, and therefore placenta cannot be considered an optimal indicator tissue for lead exposure (Lagerkvist et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…On the basis of numerous reports (Korpela et al 1986;Lagerkvist et al 1996), it is known that lead can cross the placenta and have consequences upon the developing fetus. Many older papers have proved that high doses of lead can cause miscarriage (Ernhart, 1992), and epidemiological data indicated the negative effect of lead contamination during pregnancy on newborn children and during early childhood (Shukla et al 1989).…”
Section: Leadmentioning
confidence: 99%
“…This data also showed a higher concentration of lead in the blood of boys than girls. It is well documented (Iyengar & Rapp, 2001;Lagerkvist et al, 1996;Loiacono et al, 1992), based on studies of the lead levels in maternal blood, umbilical cord blood and placenta that, that lead does not accumulate in the placenta and that the placenta does not impede, to any significant extent, the transfer of lead from the mother to the fetus. It is therefore concluded that the placenta is not suitable material for use in the monitoring of environmental lead exposure.…”
Section: Leadmentioning
confidence: 99%
“…We selected mainly trophoblastic placental tissue with no signs of calcification, avoiding the decidua basalis and chorionic plate in accordance with other recent studies. 1,12 . Falcon et al (2003) found no significant differences in the metal concentration of different trophoblastic zones analyzed from the same placenta.…”
Section: Collection Of Placental Samples and Processingmentioning
confidence: 99%